(untitled) (Journal of Medicine, 2015)
Gitelman’?s syndrome, discovered in 1966 by Gittleman,Graham and Welt, is an autosomal recessive renal tubular disorder and characterized by hypokalemic metabolic alkalosis, hypomagnesaemia, hypocalciuria. This is a rare cause of hypokalemia which has an autosomal recessive inheritance. Here we are reporting a case of a 35 years old lady presented with recurrent attacks of quadriparesis due to hypokalemia and pain in multiple joints. Later we diagnosed the case as Gitelman?’s syndrome. DOI: http://dx.doi.org/10.3329/jom.v16i1.22407 J MEDICINE 2015; 16 : 59-60